Investment Valuation of Modern Business Models - I. M. Stepnov; J. A. Kovalchuk (Учёт. Анализ. Аудит, 2021)
The paper's purpose is to identify the changes in investment decision-making processes in the hybrid (traditional and digital) economy. It is hypothesized that business models and the digital environment change the classical prerequisites for making investment decisions, and this needs to be reflected in the investment valuation. Methods of system and critical analysis, value-oriented approach are used. The predominance of competition between business models (including within ecosystems), rather than organizations, and the reduction of the investor's need for the organizational and legal design of the investment object with a variety of digital solutions are established. It is argued that the investment potential of a modern business model is influenced by the organizational architecture, the infrastructure, the value formed by the consumer, communication and interaction with the immutability of the supply. The authors developed the business model's architecture with the allocation of nine basic elements and options for investment decisions in order to reflect the increasing design complexity and individualism of the business model. New cost factors for investment evaluation of business models are identified, including digital rent, pricing approaches, digital paradox, ecosystem protection from the market, etc. The qualitative features of an effective business model are established while maintaining a quantitative assessment based on the generated cash flow. The deduction is that as the complexity of business models increases and it is possible to integrate digital business metrics and traditional financial indicators. However, at present it is advisable to maintain the existing methodology of investment assessment, supplemented with new qualitative adjustments.